Pengaruh Komitmen Organisasional, Motivasi Intrinsik Dan Disiplin Kerja Terhadap Kinerja Karyawan Kecamatan Pekalongan Selatan : Penelitian - Susi Mutiara Susanti; Arif Budiharjo (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
There is an idea to improve employee performance at the South Pekalongan District Office, Pekalongan City, Central Java Province. This is intended to provide maximum service to the community. This research aims to determine and analyze the influence of the Commitment, Intrinsic Motivation and Work Discipline variables on employee performance in the office. This research uses quantitative methods, and the type of research is causality. Data collection in this research was carried out using a questionnaire method, namely asking respondents through a questionnaire with the substance of the indicators of the variables studied. The population in this study was 61 people, and used a saturated sample or a number of populations used as all respondents. The analysis technique used is SEM-PLS. Before testing with SEM-PLS, all variables studied had gone through data validity and reliability testing, and in this process the data was classified as valid and reliable. Based on the results of hypothesis testing, it is known that organizational affective commitment, intrinsic motivation and work discipline have a significant positive effect on employee performance at the South Pekalongan District Office, Pekalongan City, Central Java Province.